2019
DOI: 10.1049/iet-pel.2018.5686
|View full text |Cite
|
Sign up to set email alerts
|

Flexible transformer‐based multilevel inverter topologies

Abstract: Cascaded multilevel inverters (MLIs) have been proposed that utilise transformers in the basic unit. The proposed inverters primarily serve to step up the input voltages in addition to using lower number of components in comparison to traditional MLIs. In order to generate all voltage levels (even and odd) at the output, three different algorithms are proposed to determine the magnitude of DC voltage sources and transformer turn ratios. Also, the basic inverter unit was further developed and two new flexible M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The issue of having several sources in an inverter can be overcome by using a transformer-based MLI (TMLI). [11][12][13][14][15][16][17][18] In TMLI, the total power required to provide an electrical load is alone supplied through a single DC source. Recent past several structures for TMLI have been presented.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The issue of having several sources in an inverter can be overcome by using a transformer-based MLI (TMLI). [11][12][13][14][15][16][17][18] In TMLI, the total power required to provide an electrical load is alone supplied through a single DC source. Recent past several structures for TMLI have been presented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] The key benefits of these TMLIs are to minimize the number of transformers, sources, and switches. Later topology in Gandomi et al 12 is suggested in high voltage and renewable energy applications. These flexible TMLI topologies have been presented to minimize component count, and these circuits use basic seven-level units to build the inverter.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Cascaded-transformer multilevel inverters (CTMIs) provide isolation through lowfrequency transformers [10][11][12][13][14][15]. They have several H-bridge converters connected in parallel to a single direct current (DC) source, while the cascaded connection is made on the secondary side of the transformers.…”
Section: Introductionmentioning
confidence: 99%